Identifikasi isolat Phytophthora asal kakao Identification of isolates of Phytophthora from cocoa - Abu UMAYAH; Agus PURWANTARA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2006)
Summary Phytophthora spp. are responsible for some serious diseases of cocoa including pod rot, stem canker, leaf blight, seedling blight, and chupon wilt. Eight species of Phytophthora have been isolated from diseased cocoa worldwide, even though only three species cause most losses in cocoa production. Twenty isolates of Phytophthora sp. were isolated from various parts of the cocoa tree collected from six cocoa producing provinces in Indonesia, viz. North Sumatera, Lampung, West Java, East Java, South Sulawesi and Southeast Sulawesi. All isolates were then identified using their morphological charac-teristics and it was concluded that all of the isolates are Phytophthora palmivora. This identification was then confirmed with molecular identification by amplification of ITS of rDNA of the isolates with primers ITS 4 and ITS 5, followed by restriction of the amplicon with enzymes. The molecular identification confirmed that all isolates are P. palmivora. Ringkasan Phytophthora spp. merupakan penyebab beberapa penyakit penting pada kakao, termasuk busuk buah, kanker batang, hawar daun, hawar bibit, dan layu tunas air. Delapan spesies Phytophthora telah berhasil diisolasi dari tanaman kakao sakit di seluruh dunia, meskipun hanya tiga spesies yang meng-akibatkan kehilangan produksi kakao yang nyata. Dua puluh isolat Phytophthora sp. telah diisolasi dari berbagai bagian tanaman kakao yang dikumpulkan dari enam provinsi sentra produksi kakao di Indonesia, yaitu Sumatera Utara, Lampung, Jawa Barat, Jawa Timur, Sulawesi Selatan dan Sulawesi Tenggara. Semua isolat diidentifikasi berdasarkan sifat-sifat morfologi dan dapat disimpulkan bahwa semua isolat adalah Phytophthora palmivora. Identifikasi selanjutnya dilakukan secara molekuler dengan amplifikasi daerah ITS dari rDNA isolat menggunakan pasangan primer ITS 4 dan ITS 5, kemudian diikuti dengan pemotongan amplikon menggunakan enzim restriksi. Identifikasi molekuler juga menun-jukkan bahwa semua isolat Phytophthora penyebab penyakit pada kakao adalah P. palmivora.